Characteristics of the COPD Patients for the Implementation of the Smartphone Application for the COPD: An Implementation Study - Ashwani Verma; Ashok Behera; Ravishankar N; Monirul Islam; Vaishali K; Mukesh Kumar Sinha; Aditya Jayaraj; Ashok Kumar Singh; Pushpendra Kumar Verma (Medsci Publications, 2024)
Background: This study provides us an opportunity to discuss about the development of a smartphone enabled Home based Self-management application for Chronic Obstructive Pulmonary Disease. Objective: To summarize the baseline characteristics of the Chronic Obstructive Pulmonary Disease patients recruited in present study. Methods: A single centered prospective non-randomized study has been conducted to implement the self-management application among 166 patients. Patients were matched based on gender and Global Initiative for Obstructive Lung Disease criteria. Smartphone application was provided to the intervention group and instructions were given to them. Results: The mean age of participants was 58.02 years in which more than half were male, more than 80% were married, almost one-third were educated up to class 10th, more than 65% have disease duration between 3 to 8 years, equally distributed for Grade 2 and 3 and two third were ex-smokers. The St. George's Respiratory Questionnaire score was 40.20 and 39.74, Clinical COPD Questionnaire score was 3.89 and 3.86, COPD Assessment Test score was 23.65 and 22.74 in intervention and control group respectively. There is no statistically significant difference between the group. Conclusion: The findings of present study provide a vital context for the follow-up results of the evaluation study.